Climate change and society in the 15th to 18th centuries. (26th March 2018) - Degroot, Dagomar
Abstract : Scholars in many disciplines have used diverse methods and sources to establish that, between the 15th and 18th centuries, a "Little Ice Age" considerably cooled Earth's climate. In four particularly chilly periods—the Spörer Minimum, Grindelwald Fluctuation, Maunder Minimum, and Dalton Minimum—falling temperatures both caused and reflected changes in atmospheric circulation that altered regional patterns of precipitation. Many scholars have argued that weather in these cold periods provoked or worsened regional food shortages, famines, rebellions, wars, and outbreaks of epidemic disease, in ways that may have contributed to mass mortality across the early modern world. More recently, some scholars have contrasted the fates of societies or communities that were "vulnerable" to climate change with those that were "resilient" or even consciously or unconsciously adaptive in the face of the Little Ice Age. Overall, research that connects climatic and social histories has suggested that human decisions, political structures, economic arrangements, institutions, and cultures either magnified or mitigated the impact of climate change on the societies of the early modern world. This article is categorized under: Climate, History, Society, Culture > Major Historical Eras Abstract : Adam van Breen, "The Vijverberg, The Hague, in Winter, with Prince Maurits and his Retinue in the Foreground, " 1618, Rijksmuseum Amsterdam.